Morphological and Hemodynamic Risk Factors for the Rupture of Proximal Anterior Cerebral Artery Aneurysms (A1 Segment) - Xu, Mingwei; Lv, Nan; Sun, Kai; Hong, Rujun; Wang, Hao; Wang, Xuhui; Xu, Lunshan; Chen, Lizhao; Xu, Minhui (Frontiers in Aging Neuroscience, 2022)
Objective The treatment of unruptured small intracranial aneurysms remains controversial. A distinguishing characteristic of A1 segment aneurysms is that they tend to rupture when they are small, which may be related to their distinctive morphology and hemodynamics. Our study sought to investigate the rupture risk factors of A1 segment aneurysms by analyzing the clinical risk factors, morphology, and hemodynamic characteristics of A1 segment aneurysms. Methods We retrospectively enrolled 49 (23 ruptured, 26 unruptured) consecutive patients presenting to our institute with A1 segment aneurysms between January 2010 and March 2020. Independent risk factors associated with the rupture of A1 segment aneurysms were analyzed by multivariate regression analysis in the ruptured group and unruptured group. Results Clinical risk factors, including age, sex, hypertension, smoking history, and SAH family history revealed no difference between the ruptured and unruptured groups. The ruptured group presented a significantly larger size (Size, P = 0.007), aspect ratio (AR, P = 0.002), size ratio (SR, P = 0.001), bottleneck index (BN, P = 0.016), dome-to-neck ratio (DN, P = 0.001), and oscillatory shear index (OSI) (P = 0.001) than the unruptured group. The normalized wall shear stress (NWSS) of the ruptured aneurysms was lower than the unruptured group (P = 0.001). In the multivariate regression analysis, only SR (OR = 3.672, P = 0.003) and NWSS (OR = 0.474, P = 0.01) were independent risk factors in the A1 segment aneurysm rupture. Conclusion A higher SR and lower NWSS revealed a close connection with the rupture of A1 segment aneurysms in our study, thus providing a reference for clinical decision-making in treating A1 segment unruptured aneurysms.